2016
DOI: 10.1159/000453669
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Effects on Dutasteride Treatment for Reducing Surgical Blood Loss during Transurethral Resection of the Prostate

Abstract: Objective: This systematic review and meta-analysis were performed to evaluate the efficacy of preoperative dutasteride treatment for reducing surgical blood loss in patients undergoing transurethral resection of the prostate (TURP). Methods: A systematic search was performed from the electronic databases including PubMed, EMBASE, and Cochrane Library by May 2016. We followed the search strategy based on Preferred Reporting Items for Systematic Reviews and Meta-analysis statement when examining the literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…However, they found that the mechanism of dutasteride in reducing blood loss is different from finasteride and dutasteride may present a time-dependent manner in reducing the MVD of the prostate. While some authors suggested 6 weeks of treatment is needed to reduce the MVD, some reported that 2 -8 weeks of dutasteride treatment has a limited effect on MVD [8]. In the present study, the lower bound of dutasteride use was 6 weeks.…”
Section: Discussioncontrasting
confidence: 47%
“…However, they found that the mechanism of dutasteride in reducing blood loss is different from finasteride and dutasteride may present a time-dependent manner in reducing the MVD of the prostate. While some authors suggested 6 weeks of treatment is needed to reduce the MVD, some reported that 2 -8 weeks of dutasteride treatment has a limited effect on MVD [8]. In the present study, the lower bound of dutasteride use was 6 weeks.…”
Section: Discussioncontrasting
confidence: 47%
“…Nowadays, most clinical nurses still estimate the color of the drainage uid based on their subjective evaluation, but there is individual difference existing among them with big deviation, unscienti c and inaccurate which may affect clinical outcomes depending on each nurse's clinical experience and skill level. In addition, some medical personnel calculate the amount of blood loss based on the red blood cell counting, hemoglobin concentration in the drainage uid or the formula to calculate the amount of blood loss [3][4][5], This way with more accurate, however, none has been widely adopted in general practice because requiring more time, more energy and increasing hospitalization costs. There are also some nursing scholars using self-made hematuria colorimetric card when assessing the degree of the hematuria, they have achieved certain success in evaluating postoperative gross hematuria , such as, using this hematuria colorimetric card can reduce anxiety levels of patients and their families and improve effective communication between doctors and nurses because they have a uni ed language [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [1] included both randomized controlled trials (RCTs) and retrospective studies in this meta-anal-…”
mentioning
confidence: 99%
“…With great interest, I read the metaanalysis by Ren et al [1] about dutasteride treatment before transurethral resection of prostate (TURP) for benign prostatic hyperplasia (BPH) patients, which was published recently. In the meta-analysis, Ren et al [1] conclude that "preoperative treatment with dutasteride could reduce surgical bleeding during TURP."…”
mentioning
confidence: 99%
See 1 more Smart Citation